Penerapan Standar Operasional Prosedur Pelayanan Restoran dalam Mengembangkan Materi Bahasa Inggris - Faradillah - Saputri; Andi Tenri Ampa; Syamsiarna - Nappu (Pusaka: Journal of Tourism, Hospitality, Travel and Business Event, 2023)
This research aims at finding out 1) the characteristics of Food and Beverage Service Management students of Makassar Tourism Polytechnic, 2) the students’ needs in English language for Food and Beverage Service based on Standard Operational Procedure, 3) the designed and developed English language materials based on Standard Operational Procedure for Food and Beverage Service Students, 4) the validity of the developed English Materials based on needs analysis of Standard Operational Procedure for Food and Beverage Service Students. This research applies Research and Development (R&D) method by using the ADDIE Model by taking 117 students of FBS Management department, Makassar Tourism Polytechnic as the respondents. The results of data analysis show that 1) The English competency level of the students of FBS Management department are mostly in the intermediate level (81.20%) 2) The language skills mostly needed by the students of FBS management department is speaking skill and they prefer to study English in the pair work or role play activity. In terms of the SOP of the restaurant services, the results have shown that all of the procedures for each SOP needed by the students of FBS as the English material for FBS Management department. 3) The English material which is designed and developed based on the need analysis of SOP restaurant services, 4) the results of the last validation for the designed and developed material indicate that the material is ready to be used. The quality of the developed materials is categorized as good material. Thus, it can be used as a main source to learn English Food and Beverage Service Management at Makassar Tourism Polytechnic